Line 7: Line 7:
 
<math>\left| az^{-1}\right|<1</math>, or equivalently <math>\left| z\right|>\left| a\right|</math>
 
<math>\left| az^{-1}\right|<1</math>, or equivalently <math>\left| z\right|>\left| a\right|</math>
  
<math>X(z)=\sum_{n=0}^{\infty}(az^{-1})^{n}=\frac{1}{1-az^{-1}}=\frac{z}{z-a}</math>
+
<math>X(z)=\sum_{n=0}^{\infty}(az^{-1})^{n}=\frac{1}{1-az^{-1}}=\frac{z}{z-a}</math>, <math>\left| z\right|>\left| a\right|</math>

Revision as of 19:50, 3 December 2008

Consider the signal $ x[n]=a^{n}u[n] $

$ X(z)=\sum_{n=-\infty}^{\infty}a^{n}u[n]z^{-n}=\sum_{n=0}^{\infty}(az^{-1})^{n} $

for convergence,

$ \left| az^{-1}\right|<1 $, or equivalently $ \left| z\right|>\left| a\right| $

$ X(z)=\sum_{n=0}^{\infty}(az^{-1})^{n}=\frac{1}{1-az^{-1}}=\frac{z}{z-a} $, $ \left| z\right|>\left| a\right| $

Alumni Liaison

Prof. Math. Ohio State and Associate Dean
Outstanding Alumnus Purdue Math 2008

Jeff McNeal